Nursing Intervention Through Family Pathnership Increases Behavior in Practice of Feeding Pattern on Infant of Age 6–24 Months For Nuclear and Extended Family - A. Aziz Alimul Hidayat (Jurnal Ners, 2010)
Introduction: Nursing intervention is nursing action with a supportive and educative approach done by nurses cooperating with families in overcoming the problems of nursing family. The aim of the research was to explain the effect of nursing intervention through family pathnership toward behavior in practice of feeding pattern on infant of age 6–24 months for nuclear and extended family, including the breastfeeding (ASI), PASI, soft food, family food, snacks, and way of feeding.Method: The design of the research was experimental. The sample of the research was ninety six (96) samples, which was chosen with simple random sampling.The sample was then divided into two parts of family in Kenjeran District and Bulak Surabaya, namely nuclear family and extended family. The variables measured were breastfeeding, PASI, soft food, family food, and a way of feeding through interviewing and observation. The data analysis used was Mann Whitney U.Result: Result showed that effect of nursing interventions on the style of feeding containing of giving PASI (p = 0.003), soft food (p = 0.005), family food (p = 0.00), snacks (p = 0.034), and way of feeding (p = 0.00). Those effects can be shown with the increasing of frequency and way of feeding before and after intervention.Discussion: The conclusion is nursing intervention through the supportive and educative approach as the form of actions on families with problems on the pattern of feeding has the influence on the practice of feeding pattern. The increasing of feeding frequency shows the cognitive and behavioral change on the practice of feeding pattern which can possibly improve the status of infants nutrient.